Pre-harvest cane burning and health: the association between school absences and burning sugarcane fields - Mauro, Carla Cabrini; Silveira Bota Ferrante, Vera Lucia; Arbex, Marcos Abdo; Ribeiro, Maria Lucia; Magnani, Romeu [UNESP] (Revista De Saude Publica, 2015)
The objective of this study was to investigate an association between pre-harvest sugarcane burning and respiratory diseases in children under five years of age. The following data were collected in five schools in the city of Araraquara, SP, Southeastern Brazil, between March and June 2009: daily records of absences and the reasons stated for these absences, total concentration of suspended particulate matter (mu g/m(3)), and air humidity. The relationship between the percentage of school absences due to respiratory problems and the concentration of particulate matter in March and from April to June presented a distinct behavior: absences increased alongside the increase in particulate matter concentration. The use of school absences as indicators of this relationship is an innovative approach.
Keywords: Preschool; Absenteeism; Respiratory Diseases, epidemiology; Smoke, adverse effects; Saccharum; Air Pollution; Particulate Matter